Enforcement of the Indonesian National Police's Code of Professional Ethics Against Police Members Who Commit Adultery or Infidelity - Yohanes Krisna Pandu Buono; Sri Endah Wahyuningsih (UNISSULA Semarang, 2025)
This study aims to determine and analyze the enforcement of the Indonesian National Police's professional code of ethics against members who commit adultery or adultery in the South Kalimantan Regional Police and the obstacles in enforcing the Indonesian National Police's professional code of ethics against members who commit adultery or adultery in the South Kalimantan Regional Police and how to overcome them. The approach method in this study is sociological juridical, the research specification is analytical descriptive. The data used are primary and secondary data and the data collection methods are field studies and literature studies, while the data analysis method uses qualitative analysis. The theory used in this study is the theory of law enforcement and legal certainty. Based on the results of the study, it can be concluded that the enforcement of the Indonesian National Police's professional code of ethics against members who commit adultery or adultery in the South Kalimantan Regional Police has been implemented by Bidpropam in accordance with Police Regulation Number 7 of 2022 concerning the Professional Code of Ethics and the Code of Ethics Commission. Obstacles in enforcing the Indonesian National Police's professional code of ethics against members who commit adultery or adultery in the South Kalimantan Regional Police are a shortage of personnel, difficult digital evidence, a culture of covering up-cover-ups, and external intervention. Solutions to these obstacles include increasing personnel in the Propam Division (recruitment and rotation), developing forensic laboratories at the regional police (Polda) level, public outreach and education on the importance of witnesses, and independent oversight (Ombudsman/NGOs) to reduce intervention.